THE IMPLEMENTATION OF MULTIMODAL PEDAGOGIES IN TEACHING WRITING IN INDONESIAN VOCATIONAL HIGH SCHOOLS - Armawan Armawan; Haryanto Atmowardoyo; Sultan Baa (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2023)
This research aimed at finding out how teachers implement multimodal pedagogies in teaching writing in the classroom. This research was conducted at one vocational high school in Biak Numfor Regency, Papua Province. The descriptive qualitative design was applied in this research. Two English teachers were chosen as participants of the study through the purposive sampling technique. The data from this research were obtained through observation, interview, and documentation. The technique of data analysis was carried out through the following steps: data condensation, data display, and conclusion drawing and verification. The results of the study showed the the teachers made some plans such as lesson plans, instructional material, learning media, and students’ worksheets. In the process of classroom teaching implementation, the teachers utilized information and communication technology to present the material. They used various learning media, such as PowerPoint, pictures, videos, and exciting learning resources, in the teaching and learning process. In evaluating teaching writing, the teachers evaluated the students’ achievement and learning process. The teachers evaluated the students’ achievement by observing them and assessing student worksheets and individual assignments. Then the teachers evaluated the learning process through self-reflection for teachers and students.